RF SYNTHESIZER WITH DIRECT DIGITAL SYNTHESIZ - V. V. Murav’iov; S. A. Korenevsky; N. M. Naumovich; A. A. Stanul (Приборы и методы измерений)
A synthesizer of frequencies with direct digital synthesis and a frequency multiplier on PLL are developed. Phase noises of an output signal of the synthesizer, noise of a loop of PLL, level of collateral radiations on outputs of the digital synthesizer (frequency of 100 MHz) and the frequency multiplier output on a loop of PLL (frequency of 8 GHz) are probed.